THE MIDDLE SEGMENT OF LEFT ANTERIOR DESCENDING ARTERY IS COMMON SITE FOR ATHEROSCLEROSIS! A STUDY BASED ON ANGIOGRAPHIC DATA - Shabana Ali; Khadija Iqbal; Sundus Ambreen (Journal of University Medical & Dental College, 2015)
ABSTRACT: OBJECTIVE: The heart receives its blood through the right and left coronary arteries, branches of the ascending aorta. The present study was conducted with the objective to determine the segment of left coronary artery involved in patients of CAD in population of Pakistan and relationship of these segments of coronary artery with age sex of patients suffering from coronary artery disease STUDY DESIGN: This was an observational study. PLACE AND DURATION OF STUDY: This study was carried out at Islamic international medical college Rawalpindi. MATERIALS AND METHODS: Data was collected from cardiology department of a government hospital in Rawalpindi. Sample size was 23 and results of cardiac patients were selected randomly. All the patients had their angiography done at the hospital. All the normal angiograms were excluded. RESULT: There was a difference in the prevalence of CAD between the male and female patients. Most of the male patients were found between 50-60 years while most female patients were between 40-50years of age. In males, middle 28.5% (3 cases) in LAD and in left circumflex artery OM-1, 21.3% (3 cases) was affected. In females, middle segment of LAD (44%) and proximal segment (22%) and OM-1 (22%) of left circumflex were most common site of blockage. CONCLUSION: There is a definite relationship between the segments of left coronary artetries with the age and sex in heart diseases so this fact should be taken into consideration by primary care physicians and interventional cardiologists